Laparoscopic Upper Pole Heminephrectomy in Adults for Treatment of Duplex Kidneys - Dönmez, Muhammet Irfan; Yazici, Mustafa Sertaç; Abat, Deniz; Kara, Önder; Bayazit, Yildirim; Bilen, Cenk Yücel (Urology Journal, 2015)
Purpose: To present our results of laparoscopic upper pole heminephrectomy in adult patients with duplex kidney. Materials and Methods: A total of 10 patients with an age range of 27 to 54 years old underwent laparoscopic upper pole heminephrectomy for complete duplication of the renal collecting system. The key point of the technique included the placement of a catheter in the normal ureter at the beginning of the procedure. The patient was positioned in a 45-90 degrees lateral decubitus position and a 4-port transperitoneal or 3-port retroperitoneal technique was applied followed by the mobilization of the upper pole ureter away from the renal hilum. Afterwards, the vasculature supplying the upper pole was precisely identified and ligated. Followed by transection of the ureter and its transposition cephalad to the hilum, the upper pole moiety was fully transected using the harmonic scalpel. Results: Eight patients were operated on using the transperitoneal approach and 2 using the retroperitoneal technique. One patient required preoperative percutaneous drainage due to pyonephrosis. The operation time ranged between 150 to 350 min with minimal blood loss (0-200 mL). Hemostasis was achieved with an Argon laser in one patient. The lower pole calyceal system was perforated in one patient and repaired intracorporally. No major intraoperative complications occurred. All of the patients except two had their drains removed in 72 h after the operation and were generally discharged on postoperative day 3. Conclusion: Laparoscopic upper pole heminephrectomy for an ectopic ureter is safe and reproducible and offers benefits of laparoscopic surgery even in patients with complicated urinary tract infection.